Stability, Control and Application of Time-Delay Systems 2019
DOI: 10.1016/b978-0-12-814928-7.00002-0
|View full text |Cite
|
Sign up to set email alerts
|

Distributed impedance control of latency-prone robotic systems with series elastic actuation

Abstract: Robotic systems are increasingly relying on distributed feedback controllers to tackle complex and latency-prone sensing and decision problems. These demands come at the cost of a growing computational burden and, as a result, larger controller latencies. To maximize robustness to mechanical disturbances and achieve high control performance, we emphasize the necessity for executing damping feedback in close proximity to the control plant while allocating stiffness feedback in a latency-prone centralized contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…As experimental evaluation, an operational space controller is implemented in a mobile base. A combination of these two studies can be found in [49].…”
Section: Related Workmentioning
confidence: 99%
“…As experimental evaluation, an operational space controller is implemented in a mobile base. A combination of these two studies can be found in [49].…”
Section: Related Workmentioning
confidence: 99%